2008
DOI: 10.1029/2008gl035867
|View full text |Cite
|
Sign up to set email alerts
|

World water tower: An atmospheric perspective

Abstract: [1] A large amount of water is stored in the world's highest and largest plateau, the Tibetan Plateau, in the forms of glaciers, snowpacks, lakes, and rivers. It is vital to understand where these waters come from and whether the supply to these water resources has been experiencing any changes during recent global warming. Here we show the maintenance of water content in the atmosphere over the Tibetan Plateau, the atmospheric circulations and transports of water vapor to this part of the world, and the trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
330
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 455 publications
(362 citation statements)
references
References 11 publications
6
330
2
4
Order By: Relevance
“…In addition, the melting water from snow and glaciers in TP is the source of many rivers in southern and eastern Asia such as Yangtze and Ganges-Brahmaputra. Therefore, the TP is also known as "the Asian water tower", supporting approximately 25 % of the world's population (Immerzeel et al, 2010;Xu et al, 2008). Quantitative estimation of the water and energy cycles over the TP is of great significance for the study of land-atmosphere-biosphere interactions, and understanding its response to climate change (Sellers et al, 1997;Yang et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…In addition, the melting water from snow and glaciers in TP is the source of many rivers in southern and eastern Asia such as Yangtze and Ganges-Brahmaputra. Therefore, the TP is also known as "the Asian water tower", supporting approximately 25 % of the world's population (Immerzeel et al, 2010;Xu et al, 2008). Quantitative estimation of the water and energy cycles over the TP is of great significance for the study of land-atmosphere-biosphere interactions, and understanding its response to climate change (Sellers et al, 1997;Yang et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…The role of the elevated high land of the Tibetan Plateau in the global water cycle was investigated by Xu et al (2008b). As seen from Fig.…”
Section: Linkage Of the Tibetan Plateau With Eastmentioning
confidence: 99%
“…1). Because of its topographic character, the plateau surface absorbs large quantities of solar radiation energy and undergoes dramatic seasonal changes in its surface heat and water fluxes (e.g., Ye and Gao 1979;Ye 1981;Yanai et al 1992;Ye and Wu 1998;Ma and Tsukamoto 2002;Hsu and Liu 2003;Yang et al 2004;Ma et al 2005;Sato and Kimura 2007;Ma et al 2008;Xu et al 2008;Cui and Graf 2009;Zhong et al 2010). Many studies have found that the east Asian monsoonal climate and the middle Asian dry climate in summer are intensified by TP mechanical and thermal forcing (e.g., Liu et al 2007).…”
Section: Introductionmentioning
confidence: 99%